By a Thread: Encoding Online Forum Data in TEI - Sebastian Reimann; Lina Rodenhausen; Frederik Elwert; Tatjana Scheffler (Journal of the Text Encoding Initiative)
Online forums are platforms where users interact in conversations organized around common topics. In this paper, we make a proposal for encoding forum data according to the TEI Guidelines using a unified format, which covers both traditional online forums as well as Reddit, the largest platform that offers forum functionality. We first discuss the specific properties of various types of forums, including most prominently their treelike thread structure. We argue that this tree structure is best represented in a nested XML tree, and does not follow existing stream- or timestamp-based CMC schemas. We present a solution that makes use of a wide range of previously available elements from the TEI Guidelines and the CMC-core schema to encode forums with different thread structures, types of post reactions, and sets of available emojis. Moreover, we propose a TEI header for storing forum metadata within the context of interdisciplinary research, which addresses the challenges of applying TEI elements to born-digital data. Finally, we propose customizations to preexisting TEI elements that are necessary to cover several peculiarities of online forums.